DAMPAK KULIAH SAMBIL BEKERJAâ (Studi Kasus Mahasiswa Universitas Riau yang Bekerja sebagai Operator Warnet) - Wensly. s, Yunus Radianto; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is to know Working while Schooling case study Students of Riau University who Work around Bina Widya Campus as Internet Cafe Operator, which is (1) Reasons of Students of Riau University in Bina Widya Campus who choose to work while have a lecture in spending their leisure time (2) Behavioral Impacts of Students of Riau University in Bina Widya Campus who work while have a lecture.The research uses qualitative descriptive approach method with phenomenology. The data sources of this research are humans (informan), activity, place and another document to support this research. Footage techniques in this research is purposive. Data collection uses direct observation, interviews and documentation. Triangulation source is used to seek the validity of the data. The analysis technique is interactive analysis model.According to the result of the research, it can be concluded that the first reasons of Students of Riau University in Bina Widya Campus working while schooling can be seen through (1) The purpose of working while schooling is fulfilling the economic needs because of the difficult family economic condition, filling their lisure time with the productive activity and intending to find a new experience. (2) Employments which are taken by Students of Riau University in Bina Widya Campus are employments that use shift system. (3) In working, Students of Riau University in Bina Widya Campus consider several things that become their reasons to choose the employment, such as a job that has flexible office hours, it does not have any special requirements for the employee, the rules as an employee are not binding, fit to skills and hobbies and consider the dormitory rules and regulations. Second, working while schooling that is done as utilizing leisure time culture has postive and negative impacts for Students of Riau University in Bina Widya Campus. The positive impacts of working while schooling are getting the new experience and the new knowledge, Capability of living independently and adding more friends or expanding the association. Whereas the negative impacts occur when students donât manage the time well. The negative impacts are attending the lectures late, being late in collecting the tasks, learning time becomes reduced, Intention to attend class is very low, low interaction with friends in the class.Keywords: The Impact Schooling while Working As Internet Cafe Operator